Coastal informal settlement and their access to electricity the case of Sitio Tondo, Barangay Digman, Bacoor City, Cavite Province, Philippines - Munarriz, Maria Lourdes T. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2014)
Urbanization and the inadequate plans for managing the influx of people and their settlements has led to the proliferation of informal settlements, even to the point of living on structures above coastal sea water. This paper explores an informal settlement in the coastal area of Bacoor City and how its residents access electricity. The site of Sitio Tondo, Barangay Digman was surveyed and the dynamics of the informal settlement examined... identifying the players in the accessibility of electricity: the informal entrepreneurs who are pioneer settlers and provide electricity to newer settlers; the government which mandates the provision of electricity to all who can pay for the services, and the profit-oriented electric firm which is tasked to come up with innovative measures for the electrification of depressed areas. The residents of Sitio Tondo consider their settlement as safe; however, urban environmental problems associated with poor housing and climate change can pose threats. The study is limited to the area but findings may be useful for future urban planning and government policy dealing with informal settlements in coastal areas.